Unique Functional Abnormalities in Youth with Combined Marijuana Use and Depression: An fMRI Study - Ford, Kristen A.; Wammes, Michael; Neufeld, Richard W.; Mitchell, Derek; Théberge, Jean; Williamson, Peter; Osuch, Elizabeth A. (Frontiers in Psychiatry, 2014)
Prior research has shown a relationship between early onset marijuana (MJ) use and depression, however this relationship is complex and poorly understood. Here, we utilized passive music listening and fMRI to examine functional brain activation to a rewarding stimulus in 75 participants (healthy controls (HC), patients with Major Depressive Disorder (MDD), frequent MJ users (MJ), and the combination of MDD and MJ (MDD+MJ)). For each participant a preferred and neutral piece of instrumental music was determined (utilizing ratings on a standardized scale), and each completed two 6-minute fMRI scans of a passive music listening task. Data underwent preprocessing and 61 participants were carried forward for analysis (17 HC, 15 MDD, 15 MJ, 14 MDD+MJ). Two statistical analyses were performed using SPM8, an ANCOVA with two factors (group x music-type) and a whole brain, multiple regression analysis incorporating two predictors of interest (MJ use in past 28 days; and Beck Depression Inventory (BDI) score). We identified a significant group x music-type interaction. Post hoc comparisons showed the preferred music had significantly greater activation in the MDD+MJ group in areas including the right middle and inferior frontal gyri extending into the claustrum and putamen and the anterior cingulate. No significant differences were identified in MDD, MJ or HC groups. Multiple regression analysis showed that activation in medial frontal cortex was positively correlated with amount of MJ use, and activation in areas including the insula was negatively correlated with BDI score. Results showed modulation in brain activation during passive music listening specific to MDD, frequent MJ users. This supports the suggestion that frequent MJ use, when combined with MDD, is associated with changes in neurocircuitry involved in reward-processing in ways that are absent with either frequent marijuana use or MDD alone. This could help inform clinical recommendations for youth with MDD.